2019
DOI: 10.1002/ana.25461
|View full text |Cite
|
Sign up to set email alerts
|

The “central vein sign” in inflammatory demyelination: The role of fibrillar collagen type I

Abstract: Accumulating evidence corroborates the role of the "central vein sign" in the radiological diagnosis of multiple sclerosis (MS). Here, we report human magnetic resonance imaging (MRI) and corresponding pathological data that inflammation-dependent intracerebral remodeling of the vessel wall is directly associated with the prominence of intralesional veins on susceptibility-based MRI. In adult marmosets with experimental autoimmune encephalomyelitis, vessel-wall fibrosis was detected early in the demyelinating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
4
15
0
1
Order By: Relevance
“…Commensurate with this, a rim of collagen deposition is seen around some of the larger blood vessels in Sirius red staining, but not in the iron staining. This observation adds evidence that the dark signal is seen around blood vessels could be a result of water exclusion from collagen deposition, ( Absinta et al, 2019 ) short T 2 * relaxation times of macro-molecules. Vascular hypointensity is commonly seen within MS lesions in the lower-resolution in-vivo scans, and is referred to as the “central vein sign.” ( Lummel et al, 2011 ; Sati et al, 2016 ) It is possible that more subtle vascular remodeling outside lesions are visible in the high-resolution, highly sensitive MRM scans reported herein.…”
Section: Discussionsupporting
confidence: 54%
“…Commensurate with this, a rim of collagen deposition is seen around some of the larger blood vessels in Sirius red staining, but not in the iron staining. This observation adds evidence that the dark signal is seen around blood vessels could be a result of water exclusion from collagen deposition, ( Absinta et al, 2019 ) short T 2 * relaxation times of macro-molecules. Vascular hypointensity is commonly seen within MS lesions in the lower-resolution in-vivo scans, and is referred to as the “central vein sign.” ( Lummel et al, 2011 ; Sati et al, 2016 ) It is possible that more subtle vascular remodeling outside lesions are visible in the high-resolution, highly sensitive MRM scans reported herein.…”
Section: Discussionsupporting
confidence: 54%
“…2 In four patients diagnosed with a systemic inflammatory disorder with involvement of the CNS (patient ID 3, 17, 27, 30), the neurological manifestation was the first manifestation of the disease. Four patients who received a diagnosis of MS had a concomitant systemic inflammatory disorder ("history of SAD" in Table 2) potentially affecting the CNS (patient ID 6,7,10,22). Of note, none of these four patients harbored MS atypical clinical, laboratory, or imaging features at the level of the CNS.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…2,5 The presence of a vein at the center of brain white matter (WM) lesions, the "central vein sign" (CVS), is a specific feature of MS and can now be depicted at clinical MRI field strength using specialized gradient-echo MRI sequences. [5][6][7] Several studies have shown how this promising imaging biomarker can differentiate MS from other disorders, including migraine, 8,9 cerebral The "central vein sign" in patients with diagnostic "red flags" for multiple sclerosis: A prospective multicenter 3T study small vessel disease, 10 neuromyelitis optica, 11 Susac syndrome, 12 and primary or secondary vasculitis of the CNS, showing similar WM lesions on MRI. 6 However, most prior studies are retrospective.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 On the contrary, inflammatory demyelinating WM lesions in MS develop around small parenchymal veins. 7 Previous studies have shown that subjects with MS have a higher proportion of lesions with a central vein compared to CSVD patients. 2,8,9 Vascular comorbidities are prevalent in MS and are associated with an increased MRI lesion burden and brain atrophy, as well as with clinical disability progression.…”
Section: Introductionmentioning
confidence: 98%